Prolonged Severe Acute Respiratory Syndrome Coronavirus 2 Delta Variant Shedding in a Patient With AIDS: Case Report and Review of the Literature. (17th September 2022) - Peters, Jillian L; Fall, Amary; Langerman, Steven D; El Asmar, Margueritta; Nakazawa, Mari; Mustapha, Aishat; Tobian, Aaron A R; Mostafa, Heba H; Blankson, Joel N
Abstract: We describe the case of a patient with AIDS who had persistent infection with a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant for >80 days. The variant contained mutations that were not present in other Delta viruses in our hospital. Prolonged infection in immunosuppressed individuals may lead to evolution of SARS-CoV-2 lineages.